PENGELOLAAN BISNIS DALAM MENGEMBANGKAN EKONOMI KREATIF PADA SANTRI YAYASAN PONDOK PESANTREN YATIM DAN DUAFA “NURUL HIKMAH” DESA LANGKO KECAMATAN LINGSAR - Oktiani, Asri; Faezal, Faezal; Syahrul, Syahrul; Maryanti, Sri; Raharja, Rizki Maulana; Irawan, Moh. Ali Yahya (LPPM Institut Pendidikan Nusantara Global, 2023)
Islamic boarding schools are educational institutions that provide teaching with the main study being Islamic religious knowledge. Islamic boarding schools are expected to be able to develop their students to be able to live independently and creatively through entrepreneurship. Managing a good business is an effort to train students to respond to the challenges and developments of the times be able to be independent with the supplies they have and be able to create jobs. This activity aims to change the mindset of how to manage business well to develop a creative economy within the Nurul Hikmah Langko Islamic boarding school environment which is a partner in community service activities. The target of this activity is students who are also studying at SMKS Islam Nurul Hikmah grades 11 and 12. The results of this activity show a change in mindset and understanding of business management and innovation towards creative and innovative businesses with the ultimate goal of developing a creative economy in the Pondok environment Nurul Hikmah Islamic boarding school in particular.